(untitled) (Studia Prawnicze / The Legal Studies, 2003)
Możliwe jest oparcie roszczenia z tytułu szkód doznanych w komunikacji elektronicznej na zasadzie winy. Zgodnie bowiem z treścią art. 415 i 416 k.c., jeżeli zawinione zachowanie organu jednostki certyfikującej pozostaje w adekwatnym związku przyczynowym z wyrządzoną komukolwiek szkodą, jednostka ta jest zobowiązana do jej naprawienia. W razie powierzenia czynności związanej z wydawaniem, zawieszaniem lub opublikowaniem certyfikatu pracownikowi lub zleceniobiorcy zastosowanie mieć będą odpowiednie postanowienia kodeksu pracy lub kodeksu cywilnego (120 k.p. oraz 429 k.c.). W tym przypadku musi istnieć związek przyczynowy między działaniem sprawcy a szkodą. Według art. 15 ustawy [z dnia 18 września 2001 r. o podpisie elektronicznym, Dz.U. Nr 130, poz. 1450 ze zm.] odbiorca usług certyfikacyjnych jest zobowiązany przechowywać dane służące do składania podpisu elektronicznego w sposób zapewniający ich ochronę przed nieuprawnionym wykorzystywaniem w okresie ważności certyfikatu służącego do weryfikacji podpisu. Należy również rozszerzyć ten obowiązek na dane służące do składania poświadczenia elektronicznego, skoro w istocie rzeczy poświadczenie to spełnia te same funkcje, co podpis elektroniczny. Podpis [elektroniczny] złożony po zajściu przesłanek zawieszenia lub unieważnienia certyfikatu, a przed dokonaniem tych czynności, pozostaje ważny i skuteczny. Wszelkie analogie do podpisu odręcznego są tutaj nie na miejscu, bo podpis może złożyć każda osoba, która weszła w posiadanie klucza prywatnego. Ryzyko złożenia takiego podpisu, albo inaczej rzecz ujmując, ryzyko postępowania stwarzającego przesłanki do pozbawienia certyfikatu mocy, obciąża co do zasady właściciela klucza podpisu. W przypadku braku uzasadnionego podejrzenia co do istnienia przesłanek unieważnienia szkodę wywołaną czasowym pozbawieniem podpisu [elektronicznego] skuteczności jest zobowiązana naprawić jednostka certyfikująca na zasadzie winy z art. 415 k.c. w związku z art. 21 ust. 4 ustawy [z dnia 18 września 2001 r. o podpisie elektronicznym, Dz.U. Nr 130, poz. 1450 ze zm.] lub na podstawie umowy dotyczącej usług certyfikacyjnych (art. 11 ust. 1 w związku z art. 5 i ust. 1 i 21 ust. 4 ustawy). W sytuacji gdy dane zawarte w certyfikacie straciły aktualność, a subskrybent nie dopełnił zastrzeżonego umownie obowiązku ich uzupełnienia, jednostka certyfikująca nie odpowiada wobec osób pokładających zaufanie w certyfikacie. Wynika to z funkcjonalnej wykładni przepisu art. 11 ust. 3 ustawy o podpisie elektronicznym. W przepisie art. 11 ustawy [z dnia 18 września 2001 r. o podpisie elektronicznym, Dz.U. 130, poz. 1450 ze zm.] zawarte jest więc domniemanie winy dłużnika (jednostki certyfikującej). Możliwa jest jednak jego egzoneracja. Przykładem okoliczności wyłączającej odpowiedzialność jest siła wyższa w postaci przerw w dostawie energii. Ze względu na szeroki charakter definicji (usługi związane z podpisem elektronicznym) w sposób niewątpliwy za usługę certyfikacyjną [art. 3 pkt 13 ustawy z dnia 18 września 2001 r. o podpisie elektronicznym, Dz.U. Nr 130, poz. 1450 ze zm.] należy uznać wszelkie czynności dotyczące procesu weryfikacji podpisu. Jeśli przykładowo w trakcie tego procesu lub przed nim pracownik podmiotu certyfikującego spowoduje wadliwość weryfikacji i nastąpi szkoda, powstają podstawy do domagania się odszkodowania. Umowa o generację pary kluczy asymetrycznych jest umową rezultatu. Wydaje się, że uzasadnione będzie odpowiednie stosowanie do umów o generację pary kluczy przepisów o umowie o dzieło. Podmiot certyfikujący nie odpowiada wobec odbiorców usług za szkody wynikające z użycia certyfikatu poza zakresem określonym w polityce certyfikacji. Przesłanką wyłączenia tej odpowiedzialności jest konieczność zawarcia w certyfikacie odnośnika (np. w postaci linku) do polityki certyfikacji. Z umowy o wydanie certyfikatu i innych dotyczących go informacji, udzielanych na podstawie art. 14 ustawy o podpisie elektronicznym, wynikają zakres i ograniczenia stosowania certyfikatu. W razie użycia certyfikatu poza wyznaczonym zakresem odpowiedzialność jednostki certyfikującej jest wyłączona. Ograniczenie zakresu stosowania certyfikatu może dotyczyć, tak samo jak zawężenie możliwości używania podpisu elektronicznego, określonych typów kontraktów lub kontraktów o określonej wartości. Dopuszczalne jest także podmiotowe ograniczenie zastosowania certyfikatu, jeżeli oczywiście obie strony umowy się na to zgodzą. Chodzi tu o zastrzeżenie umowne, na mocy którego jednostka certyfikująca i subskrybent postanawiają, iż certyfikat może wykorzystać tylko określona osoba lub osoby albo określona kategoria osób (np. osoby fizyczne). It is possible to base a claim for damages suffered in electronic communications on the principle of fault. Indeed, according to Articles 415 and 416 of the Civil Code, if the culpable behaviour of an authority of a certification body is in an adequate causal relationship with the damage caused to anyone, that body is obliged to compensate for it. If the activity of issuing, suspending or publishing the certificate is entrusted to an employee or contractor, the relevant provisions of the Labour Code or the Civil Code (Article 120 of the Labour Code and Article 429 of the Civil Code) will apply. In this case, there must be a causal link between the offender’s action and the damage. According to Article 15 of the Act [of 18 September 2001 on electronic signature, Journal of Laws No. 130, item 1450. as amended] the recipient of certification services is obliged to store the data used for affixing an electronic signature in a manner ensuring its protection against unauthorised use during the validity period of the certificate used to verify the signature. This obligation should also be extended to the data for the electronic certification, since in essence this certification fulfils the same functions as an electronic signature. An [electronic] signature affixed after the prerequisites for suspension or revocation of a certificate, and before these actions have taken place, shall remain valid and effective. Any analogy to a handwritten signature is out of place here, as a signature can be made by any person who has come into possession of a private key. The risk of such a signature, or, to put it another way, the risk of conduct creating grounds for de-certification, is in principle borne by the owner of the signature key. In the absence of a reasonable suspicion of the existence of grounds for invalidation, the damage caused by temporary deprivation of [electronic] signature effectiveness is liable to be repaired by the certification authority on the basis of fault pursuant to Article 415 of the Civil Code in connection with Article 21(4) of the Act [of 18 September 2001 on electronic signature, Journal of Laws No. 130, Item 1450, as amended] or on the basis of an agreement on certification services (Article 11(1) in connection with Article 5(1) and Article 21(4) of the Act). In a situation where the data contained in the certificate has become out-of-date and the subscriber has not fulfilled a contractually stipulated obligation to complete it, the certification body shall not be liable to persons placing their trust in the certificate. This follows from a functional interpretation of the provision of Article 11(3) of the Act on electronic signature. The provision of Article 11 of the Act [of 18 September 2001 on electronic signature, Journal of Laws No. 130, item 1450, as amended] therefore contains a presumption of fault on the part of the debtor (certification body). However, its exoneration is possible. An example of a circumstance excluding liability is force majeure in the form of power cuts. Due to the broad nature of the definition (services related to the electronic signature), undoubtedly a certification service [Article 3(13) of the Act of 18 September 2001 on electronic signature, Journal of Laws No. 130, item 1450, as amended] certification service should be regarded as all activities concerning the signature verification process. If, for example, during or before this process, an employee of the certification body causes a defect in the verification and damage occurs, grounds for claiming compensation arise. An agreement for the generation of an asymmetric key pair is an agreement of result. It would seem reasonable to apply the provisions of a contract for specific work in agreements for the generation of a key pair. The certification body shall not be liable to the recipients of the services for damages resulting from the use of the certificate outside the scope specified in the certification policy. The rationale for excluding this liability is that a referral (e.g. in the form of a hyperlink) to the certification policy must be included in the certificate. The scope and limitations of the use of the certificate are derived from the certificate agreement and other information concerning it, provided pursuant to Article 14 of the Act on electronic signature. If the certificate is used outside the designated scope, the certification body’s liability is excluded. Restricting the scope of use of a certificate can apply, as can restricting the use of an electronic signature, to certain types of contracts or contracts of a certain value. A subjective limitation on the application of the certificate is also permissible if, of course, both parties to the contract agree. This is a contractual stipulation whereby the certification body and the subscriber agree that the certificate can only be used by a specific person or persons or a specific category of persons (e.g. natural persons).